Empowering Parents in Improving Knowledge and Skills of Sex Education for Children at An-nashiriyyah Kindergarten Ciledug Tangerang City - fratidhina, yudhia; Karningsih, Karningsih; Farinsha, Citra (jitek, 2024)
ABSTRACT Background: Sexual education is education that teaches about feared sexual activities to avoid sexual violence. Child sexual violence will increase by 30% in 2023 due to lack of knowledge and skills from parents. Parents' knowledge and skills can be improved by parental empowerment. Research Objective: Knowing the influence of parental empowerment on knowledge and skills about sex education in children at An-nashiriyyah Kindergarten Ciledug, Tangerang City. Research Method: A type of quasi-experimental quantitative research with a one group pretest-posttest research design.The sample was taken using non-probability sampling as many as 60 samples. The analysis used an Independent T Test with a significance of α<0.05. Results: There is a significant influence on parents' knowledge and skills about sex education in children seen from the T-Independent Test getting a p-value of 0.000 where the value is <0.05 with a confidence level of 95%. Discussion: Parental empowerment makes the delivery of information more enjoyable because it is done simultaneously with practice or play so that information is more conveyed and effective in improving knowledge and skills.